Botlhoko, botlhoko! How people talk about their musculoskeletal complaints in rural Botswana: a focused ethnography - Maria Hondras; Corrie Myburgh; Jan Hartvigsen; Helle Johannessen (Taylor & Francis Group, 2015)
Background: Conflicting interpretations about the structure and function of the body contribute to discordance in communication between healthcare professionals and lay people. Understanding musculoskeletal (MSK) complaints presents additional complexities when discussed in more than one language or in cross-cultural settings. In low- and middle-income countries (LMICs), few healthcare professionals have specialist MSK training and not all practitioners speak the primary language of patients. Objective: Our goal was to understand how people in rural Botswana perceive and express MSK complaints. Design: Ethnographic fieldwork for 8 months in the Botswana Central District included participant observations and interviews with 34 community members with MSK complaints. Audio-recorded interviews were typically conducted in Setswana with an interpreter, transcribed verbatim, and contextually translated into English. Abductive qualitative analysis was used as the interpretive methodology. Results: Whereas initial responses about MSK troubles yielded the exclamation botlhoko, botlhoko! combined with animated non-verbal gestures and facial expressions indicating widespread body pains, in-depth interviews revealed the complexities of pain expression among respondents. MSK pains were described as 'bursting, exploding, aching, numbness, hot, pricking, stabbing, swollen, and pain in the heart'. Language subtleties manifested during interviews, where 'meat' or 'flesh' implied soft tissue pains; waist pains were voiced yet portrayed as low back or sacroiliac pain; and 'veins' variously referred to structural and functional types of pain. Psychological and social stressors accompanied many accounts of MSK troubles. Conclusions: Respondents offered diverse MSK symptom descriptions consistent with biopsychosocial illness models, yet few communicated complaints using the biomedical language of healthcare providers. Although research interview and transcription processes may not be practical for clinicians, working with interpreters who communicate detailed patient accounts for MSK troubles will complement patient-provider encounters. Community member perceptions of their MSK pain and associated conditions should be explored and incorporated into healthcare interventions and innovations for rural communities in LMICs.